Plasma Cell Gingivitis Due to an Antitartar Toothpaste: An Unusual Case Report - Manoj Kumar1, Lora Mishra2, Rinkee Mohanty3, Rashmita Nayak4, Saurav Panda1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Plasma cell gingivitis is a rareform of atypical gingival inflammation which is characterized by erythematousmarginal gingival hypertrophy which may involve the adjacent attached gingiva. Plasma cell gingivitis(PCG) is an atypical form of gingivitis and is characterized by massive infiltration of plasma cells intothe subepithelial connective tissue. It is a rare condition; the cause of which is still not fully understood.It is often attributed to an allergic reaction to the components of chewing gums, dentifrices or various dietcomponents. A case of PCG is presented here in a 52 -year old male who switched to an anti-tartar toothpasteon the advice of a dentist which manifested in a generalized form. This report is the first, as far as we know,that relates PCG to the use of Glister toothpaste manufactured by Amway. The histological examinationrevealed the infiltration of polyclonal plasma cells. The PCG disappeared within two weeks of stopping theuse of the dentifrice.